2010
DOI: 10.1556/jep.8.2010.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Environment, methodology, and the object choice task in apes: Evidence for declarative comprehension and implications for the evolution of language

Abstract: Abstract. The ability to comprehend purely informative (declarative) communications has been put forward by several researchers as a possible biological distinction between humans and our nearest evolutionary relatives, the great apes. Most studies that purport to show that great apes cannot comprehend declaratives utilize the object choice task as a basis of measurement and have relatively few subjects. Here we report on a large-scale study of chimpanzees and bonobos as well as a meta-analysis of earlier stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 32 publications
4
35
2
Order By: Relevance
“…It is possible that with an increased sample of language-using apes, this difference would be significant. These results and the differences noted above are consistent with our previous findings that rearing and living environment greatly affect the cognitive and communicative capacities of apes (Lyn 2010; Lyn et al 2010; Russell et al 2011; Leavens and Bard 2011; Leavens et al 2010b). However, in the current study, the species variable is confounded with rearing differences, so further research is required to distinguish the cause of these differences.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is possible that with an increased sample of language-using apes, this difference would be significant. These results and the differences noted above are consistent with our previous findings that rearing and living environment greatly affect the cognitive and communicative capacities of apes (Lyn 2010; Lyn et al 2010; Russell et al 2011; Leavens and Bard 2011; Leavens et al 2010b). However, in the current study, the species variable is confounded with rearing differences, so further research is required to distinguish the cause of these differences.…”
Section: Discussionsupporting
confidence: 93%
“…The bonobos also had pre-experimental communicative interactions about items that were not just out of sight, but had happened in the past, or were planned for the future (Lyn et al 2011; Brakke and Savage-Rumbaugh 1996; Savage-Rumbaugh et al 1986). Although several studies have shown that apes reared in a socio-linguistic environment have a better understanding of communicative points by their caregivers (see Lyn 2010; Lyn et al 2010; Russell et al 2011), we do not have any evidence that this impacted performance in this displacement task.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…The bonobos also had pre-experimental communicative interactions about items that were not just out of sight, but had happened in the past, or were planned for the future Brakke and Savage-Rumbaugh 1996;Savage-Rumbaugh et al 1986). Although several studies have shown that apes reared in a socio-linguistic environment have a better understanding of communicative points by their caregivers (see Lyn 2010;Lyn et al 2010;Russell et al 2011), we do not have any evidence that this impacted performance in this displacement task.…”
Section: Discussioncontrasting
confidence: 74%
“…For many years it was thought that apes systematically failed at the object choice task [Povinelli et al, 1990; Call et al, 1998]. A re-evaluation of the evidence in two recent reviews suggests, however, that a cue that is presented centrally can distract subjects and indeed the proportion of positive findings in experiments with peripheral cues is higher [Lyn, 2010; Mulcahy & Hedge, 2012]. …”
Section: Introductionmentioning
confidence: 99%